2023
DOI: 10.1111/echo.15662
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of subclinical left ventricular systolic dysfunction in patients with asymptomatic severe aortic stenosis with preserved left ventricular systolic function by three‐dimensional speckle tracking echocardiography

Abstract: ObjectivesLeft ventricular dysfunction and remodeling can occur as a result of aortic valve stenosis (AS). Three‐dimensional speckle tracking echocardiography (3D‐STE) can detect early left ventricular myocardial dysfunction even before ejection fraction declines. The purpose of this study was to look at the relationship between various myocardial strain parameters measured by 3D‐STE in asymptomatic severe AS patients from Bangladesh.MethodsThis study included 46 patients with asymptomatic severe AS but preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Also, studies have shown that more than 80% of deaths in asymptomatic patients occur before reaching the guideline-recommended threshold for surgical intervention ( 130 , 131 ). Hence, as in other settings of subclinical dysfunction, LVEF is not a sensitive marker of early LV systolic dysfunction compared with longitudinal and circumferential LV strains in identifying patients with impaired LV function, who require AVR, despite preserved LVEF ( 132 134 ).…”
Section: Limitations Of Lvef In Heart Valve Diseasementioning
confidence: 95%
“…Also, studies have shown that more than 80% of deaths in asymptomatic patients occur before reaching the guideline-recommended threshold for surgical intervention ( 130 , 131 ). Hence, as in other settings of subclinical dysfunction, LVEF is not a sensitive marker of early LV systolic dysfunction compared with longitudinal and circumferential LV strains in identifying patients with impaired LV function, who require AVR, despite preserved LVEF ( 132 134 ).…”
Section: Limitations Of Lvef In Heart Valve Diseasementioning
confidence: 95%